2015
DOI: 10.1038/mt.2014.233
|View full text |Cite
|
Sign up to set email alerts
|

Functional Aspects of Intrahepatic Hepatitis B Virus-specific T Cells Induced by Therapeutic DNA Vaccination

Abstract: Current therapies for the hepatitis B virus (HBV), a major cause of severe liver disease, suppress viral replication but replication rebounds if therapy is withdrawn. It is widely accepted that immune activation is needed to control replication off-therapy. To specifically activate T cells crossreactive between the hepatitis B core and e antigens (HBcAg/HBeAg) in chronically infected patients, we developed a therapeutic vaccine candidate. The vaccine encompass codon-optimized HBcAg and IL-12 expressing plasmid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…To evaluate the immunogenicity of the constructs in vivo, mice and rabbits were immunized essentially as described [ 25 , 30–32 ], boosted at monthly intervals, and sacrificed 2 weeks later for spleens and blood collection. In brief, female C57BL/6 mice (5 per group) were immunized intramuscularly in the tibialis cranialis anterior muscle with 50 μg plasmid DNA in a volume of 50 μL in sterile phosphate-buffered saline (PBS) by regular needle (27G) injection followed by in vivo electroporation using a Cliniporator 2 device (IGEA).…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the immunogenicity of the constructs in vivo, mice and rabbits were immunized essentially as described [ 25 , 30–32 ], boosted at monthly intervals, and sacrificed 2 weeks later for spleens and blood collection. In brief, female C57BL/6 mice (5 per group) were immunized intramuscularly in the tibialis cranialis anterior muscle with 50 μg plasmid DNA in a volume of 50 μL in sterile phosphate-buffered saline (PBS) by regular needle (27G) injection followed by in vivo electroporation using a Cliniporator 2 device (IGEA).…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that in vivo ET greatly improves transfection efficacy and immunogenicity of DNA vaccines. 11–13 We first evaluated whether different pulse pattern for the in vivo ET had an impact on the transfection efficacy and immune activation. A high–low pulse combination pattern induced a high transfection rate, influx of CD3+ cells, and a strong T-cell response.…”
Section: Discussionmentioning
confidence: 99%
“…in the tibialis cranialis muscle once with doses of 50, 20, or 5 μg plasmid DNA ( e.g. , coNS3/4A-pVAX1 or C2.2-pVAX1-pVAX1) alone or in combination with 5 μg mIL-12-pORF1 12 in a volume of 30 μl using the IVIN or regular needle injection. Immediately following administration of the plasmid DNA, tibialis cranialis muscles were subsequently electrotransferred using the Cliniporator 2 device (IGEA) with two 60 ms 246 V/cm pulses or 1 ms 600 V/cm pulse followed by a 400 ms 60 V/cm pulse pattern.…”
Section: Methodsmentioning
confidence: 99%
“…Groups of mice were immunized by the intramuscular (i.m.) route using a regular needle or using the in vivo intracellular injection device (IVIN) 45 . All immunizations were performed in the left tibialis cranialis muscle.…”
Section: Methodsmentioning
confidence: 99%